Modified zeolite beta as catalysts in friedel-crafts alkylation of resorcinol - Abd. Mazak, Marzita (2006)
Zeolites are widely used as acid catalysts for the synthesis of fine chemicals in industrial processes. One such process is Friedel-Crafts alkylation which proceeds in the presence of acid catalysts. In this research, the acid property of zeolite Beta was studied in order to increase its activity in the Friedel-Crafts alkylation of resorcinol with tert-butanol. Zeolite Beta was chosen as catalysts in the Friedel- Crafts alkylation because it possesses large pore and high acid strength. Zeolite Beta was modified by varying the SiO2/Al2O3 ratios of the initial gel and introducing niobium oxide into zeolite Beta samples. All samples were characterized by XRD, FTIR, N2 adsorption, UV-Vis DR and 29Si MAS NMR. XRD results showed all samples gave highly pure zeolite Beta phase. 29Si MAS NMR showed that the zeolite Beta samples with initial SiO2/Al2O3 ratios = 27, 45 and 90 result in the zeolite Beta having Si/Al framework ratios of 11, 21 and 19 respectively. The crystallinity of zeolite Beta is slightly decreased after the introduction of niobium oxide into the samples. UV-Vis DR results showed that the niobium species in zeolite Beta samples are mainly in the tetrahedral form. Acidity study of the catalysts was measured by FTIR pyridine adsorption and TPD of ammonia. FTIR pyridine showed that the amount of Brönsted acid sites in zeolite Beta samples increased in the order of framework Si/Al ratios = 21 < 19 < 11 and also increased after 2 % wt Nb loading but decreased after 4 % Nb loading. Meanwhile the Lewis acid site did not showed any correlation to the Si/Al ratios of zeolite Beta but increased after incorporated with niobium. TPD results showed that the amount of acid sites in zeolite Beta samples decreased while the acid strength increased with the increased of Si/Al ratios of zeolite Beta framework. The strength and the amount of acid sites also increased after 2 % wt Nb loading and decreased after 4 % wt Nb loading. All catalysts were tested in Friedel-Crafts alkylation of resorcinol with tert-butanol. GC analysis showed the alkylation of resorcinol over zeolite Beta at different Si/Al ratios produced 4,6-di-tert-butylresorcinol (main product) and 4-tert-butylresorcinol. The conversion decreased in the order, zeolite Beta with Si/Al = 11 (95 %) > 19 (70 %) > 21 (64 %) and the selectivity of 4,6-di-tert-butylresorcinol also decreased in the order Si/Al= 11 (81 %) > 19 (78 %) > 21 (56 %). Zeolite Beta sample with Nb loading has successfully produced 4,6-di-tert-butylresorcinol with 100 % selectivity. ESR analysis showed that the alkylation product containing butylated resorcinol is 4 times stronger antioxidant than the resorcinol itself.